THE ORIGIN OF THE SIJO (時調) POETIC FORM IN RELATION TO OLD KOREAN MUSIC SCORES - Jaemin, Park; Jinhee, Kim (Acta Koreana, 2017)
This article examines the origin of the sijo form based on the traditional Korean music scores such as mandaeyŏp (慢大葉, fifteenth to sixteenth century music) and chinjak 1 (眞勺一, twelfth to fifteenth century music) and estimates that sijo originated in the late fifteenth to sixteenth centuries. It is commonly believed that sijo originated in hyangga or Koryŏ kayo and has been sung and enjoyed since the late Koryŏ dynasty (高麗, 918–1392). However, this common perception lacks empirical evidence. Sijo is a sung form and its music originated from the mandaeyŏp (慢大葉) song, so an examination of its musical background is necessary to provide solid evidence to determine its origin. Some researchers have argued that the first sijo song, mandaeyŏp (慢大葉), originated from chinjak 3, but have not provided specific evidence of the relationship between the two compositions. This research investigates the derivation of mandaeyŏp from chinjak 1 (眞勺一) rather than chinjak 3 (眞勺三) on the basis of clear similarities in form and melody between the two types of composition. Because mandaeyŏp shows such concrete influences from chinjak 1 in Taeak hubo (大樂後譜), a collection of popular songs during King Sejo’s reign (世祖, r. 1455–1468), readers have inferred that the time of derivation of mandaeyŏp is close to that of chinjak 1. In fact, mandaeyŏp scores did not emerge before King Sejo’s reign, during the late fifteenth century, but appeared continuously after his reign. Looking at the problem from a literary perspective, sijo poems initially emerged in munjip (文集), or literati’s private collections, and their poetic form is intricately connected with the mandaeyŏp score. This consistent evidence clearly shows that the sijo form originated and developed under the influence of mandaeyŏp scores around the late fifteenth century.